2018
DOI: 10.1088/1361-6463/aad1ca
|View full text |Cite
|
Sign up to set email alerts
|

N2 dissociation and kinetics of N(4S) atoms in nitrogen DC glow discharge

Abstract: N2 dissociation in pure nitrogen plasma has a long history of research. It seems to be a complex process which comprises many reactions involving various electronic and vibrational nitrogen states whose contributions can vary depending on conditions. In this paper, we studied N2 dissociation in the stationary N2 discharge both experimentally and theoretically. We used a DC glow discharge in a quartz tube in pure N2 at moderate pressures (5–50 Torr). The degree of dissociation, atomic nitrogen loss rate and gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 136 publications
3
49
0
Order By: Relevance
“…[4] A large fraction of the energy dissipated in N 2 plasmas at reduced fields, typical of DBDs, goes into vibrationally excited states. [5] Adverse consequences are comparably high voltages necessary to drive N 2 DBDs and excessive (vibrational) heating of the gas.…”
Section: Introductionmentioning
confidence: 99%
“…[4] A large fraction of the energy dissipated in N 2 plasmas at reduced fields, typical of DBDs, goes into vibrationally excited states. [5] Adverse consequences are comparably high voltages necessary to drive N 2 DBDs and excessive (vibrational) heating of the gas.…”
Section: Introductionmentioning
confidence: 99%
“…Discharge current density at the cathode (j~0.4 mA cm −2 ) and measured cathode temperature T c = 310 K hints at an abnormal regime of the discharge operation. Based on plasma-chemical and electron kinetics calculations of N 2 plasma 24 we estimate the electron and ion concentration n e ≈ n i ~10 8 cm −3 , reduced electric field E/N~55 T d and respective electron temperature T e ~1 eV in positive column between the cathode and sample surfaces. In these conditions, N atoms in ground N( 4 S) and lowest metastable N( 2 D) and N( 2 P) states are effectively produced in N 2 dissociation by electron impacts.…”
Section: Discussionmentioning
confidence: 99%
“…The measured N atoms density was higher than those obtained in all Ar/N 2 mixtures. In pure nitrogen, it has been shown that the production of N atoms may occur through several processes which can be summed up in two categories: dissociation of the ground state molecules (at different vibrational levels, v) N 2 (X 1 Σ + g , v) by electron impact, and collisions of N 2 molecules that are excited in various electronic and vibrational states 44 . While it is difficult to estimate the dominant dissociative processes in our case, since we are not aware of the existence of an extensive model of our peculiar discharge in nitrogen, it is possible that Ar atoms are not completely detrimental to a nitrogen discharge.…”
Section: Influence Of the Gas Mixturementioning
confidence: 99%